THE PORTRAYAL OF MODERN WOMEN IN BAHMANYOR’S SHAHANSHAH: A COMPARATIVE ANALYSIS OF URBAN AND RURAL FEMININITY IN TAJIK LITERATURE (Scientific journal of the Fergana State University, 2026)
Bahmanyor, a prominent Tajik male author, stands out for his nuanced exploration of women and femininity in his literary works, particularly in Shahanshah. This novel introduces the archetype of the modern urban Tajik woman, contrasting her with traditional rural women and historical female figures. Through the characters of Chisto and Sito, two sisters embodying contemporary freedoms, Bahmanyor examines the evolving social liberties of Tajik women. This paper analyzes the depiction of these urban women, their independence, and their juxtaposition with historical and rural female archetypes, situating Shahanshah within the broader context of Tajik and post-Soviet literature.